ABTAS: An Automated Baggage Tracking and Alert System using RF Technology - Agnal, A. Sharmila; Saraswathi, E.; Saravanan, M.; Subha, K. (International Journal of Engineering and Technology, 2026)
Radio Frequency (RF) is a challenging technology that has been used for providing accurate solutions for many kinds of societal issues. This paper focuses on developing an automated device named “ABTAS” to identify and track the location of passengers’ luggage during their travel or any theft by applying RF technology. The proposed system analyzes the use of an interactive RF transmitter and receiver that communicates with each other in tracking objects. The proposed system also deals with the tracking of missed luggage by sending a SMS alert to the passenger by using GSM.